Centripetal-Centrifugal Forces in the Tower of Babel Narrative (Gen 11:1–9) - Putrawan, Bobby Kurnia; Noya, Ludwig; Negoro, Alisaid Prawiro (Old Testament Essays, 2022)
This article argues that the Tower of Babel’s narrative (Gen 11:1–9) serves as a counter narrative against the universalisation of language, territory and peoplehood identity. In addition, it perfectly fits the politics of Israelite identity formation throughout the book of Genesis. The argument is anchored as follows: Firstly, the article surveys the earlier interpretations of scholars. Secondly, it examines the Tower of Babel narrative as a subversive narration for identity formation by analysing the interaction of language, territory and identity in the narrative. Lastly, Gen 11:1 –11 text is read within the larger narrative in the book of Genesis utilising the concept of centripetal and centrifugal forces proposed by Mikhail Bakhtin. In so doing, this article shows that the Tower of Babel narrative employs such a force to subvert the imperial propaganda of unification and advances its own agenda of identity politics. https://doi.org/10.17159/2312-3621/2022/v35n2a5